2010
DOI: 10.1248/yakushi.130.1053
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Sinomenine on Cartilage Degradation and Chondrocytes Apoptosis

Abstract: Sinomenine (SIN), an alkaloid extracted from the stem of the Chinese medicinal plant sinomenium acutum, has been used for treating rheumatoid arthritis. But little is known whether SIN has a protective eŠect on osteoarthritis (OA). In this study, we investigated the protective eŠect of SIN on IL-1b-induced proteoglycan degradation and apoptosis in rabbit articular cartilage and chondrocytes. Treatment with 10 ng/ml IL-1b increased the level of glycosaminoglycan (GAG) released into the culture media, and up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Therefore, prevention of excessive apoptosis of chondrocytes is believed to be beneficial for OA management. Drugs that can ameliorate OA have been reported to show anti-apoptotic effects on chondrocytes, such as sinomenine (Ju et al 2010), ADAM15 (Böhm et al 2010) and amiloride (Rong et al 2011). Many triterpenoid saponin ingredients in traditional Chinese medicine have anti-apoptotic effects, such as astragaloside (Shang et al 2011), Panax notoginseng saponins , Ginsenoside-Rg2 (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prevention of excessive apoptosis of chondrocytes is believed to be beneficial for OA management. Drugs that can ameliorate OA have been reported to show anti-apoptotic effects on chondrocytes, such as sinomenine (Ju et al 2010), ADAM15 (Böhm et al 2010) and amiloride (Rong et al 2011). Many triterpenoid saponin ingredients in traditional Chinese medicine have anti-apoptotic effects, such as astragaloside (Shang et al 2011), Panax notoginseng saponins , Ginsenoside-Rg2 (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that SIN exhibited a wide range of pharmacological actions including anti-inflammatory, anti-rheumatic, immunosuppressive, analgesic and antiarrhythmic effects (Shu et al, 2007;Teng et al, 2012;Song et al, 2013). And there are many other researches indicate that SIN has many pharmacological characters such as inducing apoptosis and anti-angiogenesis effect what has been treated as means of treating colon carcinoma (Kok et al, 2005;Ju et al, 2010;Chen et al, 2011).…”
Section: Suppressive Effect Of Sinomenine Combined With 5-fluorouracimentioning
confidence: 99%
“…Many reports show that SIN has the potent of inhibiting proliferation and inducing apoptosis on chondrocytes (Ju et al, 2010), CD4+ T cells (Shu et al, 2007), monocytes (Jiang et al, 2007) and tumor cells (Jiang et al, 2010). But the specific mechanism about how SIN inducing apoptosis has not been researched clearly.…”
Section: Evaluation Of Side Effectsmentioning
confidence: 99%
“…Many researches have demonstrated that enzymatic cleavage by MMPs together with pro-inflammatory cytokines plays critical roles in the initiation and progression of cartilage destruction (Ju et al, 2010). The results of this study demonstrated that the contents of PGE2 , NO, TNF-α, IL-6 and IL-1β in synovia and expressions of MMP-3, MMP-13 in cartilage were elevated in OA model group, whereas the elevation of PGE2 , NO, TNF-α, IL-6, IL-1β, MMP-3 and MMP-13 levels were significantly suppressed in SSG groups.…”
Section: Discussionmentioning
confidence: 99%